Pencegahan Dan Penanganan Stunting Desa Laburan Baru Kecamatan Paser Belengkong - Reza Fahrepi (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
Laburan Baru Village is one of the villages under the working area of ​​Paser Belengkong District which is one of the stunting locus villages. Community Service by providing material related to handling and preventing stunting in Laburan Baru Village, Paser Belengkong District. Counseling or material for handling and preventing stunting is carried out through lecture methods and question and answer discussions. The target of this activity is for all community members in Laburan Baru Village, Paser Belengkong District to understand more about the dangers of stunting for children's growth and development. In this activity, the importance of good cooperation between cross-sectors to deal with stunting was also conveyed, whether as community members, village officials, health centers, and all parties must work together in handling and preventing stunting.